EFFECTS OF GLOBAL WARMING - Jain, Basanti (International Journal of Research -GRANTHAALAYAH, 2015)
The abnormal increase in the concentration of the greenhouse gases is resulting in higher temperatures. We call this effect is global warming. The average temperature around the world has increased about 1'c over 140 years, 75% of this has risen just over the past 30 years. The solar radiation, as it reaches the earth, produces "greenhouse effect" in the atmosphere. The thick atmospheric layers over the earth behaves as a glass surface, as it permits short wave radiations from coming in, but checks the outgoing long wave ones. As a result, gradually the atmosphere gets heated up during the day as well as night. If such an effect were not there in the atmosphere the ultraviolet, infrared and other ionizing radiations would have also entered our atmosphere and the very existence of life would have been endangered. The ozone layer shields the earth from the sun's harmful ultraviolet radiations. The warm earth emits long wave (infrared) radiations, which is partly absorbed by the green house gaseous blanket. This atmospheric blanket raises the earth’s temperature.